(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
The research aim is to develop teaching materials for English writing skills based on Creative, Active, Systematic, and Effective (CASE) for Elementary School Students in Tangerang City. Creative, Active, Systematic, and Effective (CASE) based teaching materials are learning resources that can direct students to learn creatively, actively, systematically, and effectively so they can gain maximum knowledge and understanding of the material. The research method used in this study uses Research and Development (R&D) using the Dick & Carey approach. The subjects of this study were fourth grade students from SDN Cikokol 4 Tangerang. The instrument in this study was a product assessment questionnaire given to students, teachers, and media expert, material expert as well as English language experts. The result indicated that the product of material development gained average of 82,4% or in category of very sufficient, and the pretest posttest result was t-count 2,319 > t-table 2,048. In other words, it can be concluded that there was a significant different score between pretest and posttest in terms of writing skills. Thus, it can be stated that the product of materials development can be used in the teaching learning English and can develop students writing skills effectively.